2012
DOI: 10.1100/2012/450619
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence Survey of American Trypanosomiasis in Central Valley of Toluca

Abstract: American trypanosomiasis is a growing health issue in the Americas. México is an endemic country, where some locations such as in the State of México are considered highly prevalent. In the valley of Toluca city, the capital of the State of Mexico, there exists an apparent high prevalence in dogs. The absence of triatomine vectors suggests that dogs may not be infected. Therefore, we conducted a directed survey to domiciliated and nondomiciliated dogs to reassess dogs' T. cruzi seroprevalence status. HAI and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Furthermore, northern Mexico City has optimal conditions for the development of different species of the T. cruzi vector. In a study by Quijano‐Hernández et al 2011, they reported that the high‐risk areas for Chagas disease were in the rural places that were below 2,000 meters above sea level . In an earlier study, by Salazar‐Schettino et al 2005, they reported the presence of T. barberi in different states at a height of more than 2,400 meters above sea level that included Mexico City and Hidalgo .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, northern Mexico City has optimal conditions for the development of different species of the T. cruzi vector. In a study by Quijano‐Hernández et al 2011, they reported that the high‐risk areas for Chagas disease were in the rural places that were below 2,000 meters above sea level . In an earlier study, by Salazar‐Schettino et al 2005, they reported the presence of T. barberi in different states at a height of more than 2,400 meters above sea level that included Mexico City and Hidalgo .…”
Section: Discussionsupporting
confidence: 89%
“…Photographs were taken in rural areas of the municipalities of Tremedal (A and B) and Irecê, Bahia, Brazil (E-F) (DTU). In Mexico, a study conducted in 2010 reported a prevalence of 34% [31], while another study carried out in 2017 detected a prevalence of 4.4% [32]. Other studies conducted in Mexico have reported different prevalence values [33][34][35][36][37][38][39][40][41][42][43].…”
Section: Trypanosoma Cruzi Infection and CD In Dogsmentioning
confidence: 98%
“…5 ), which may be partly attributed to the variability in terms of transmission risk, but also to sample size and serological tests used by different research groups to detect anti- T. cruzi antibodies in dogs, as well as to the genetic variability of the circulating T. cruzi strains (discrete typing units (DTU). In Mexico, a study conducted in 2010 reported a prevalence of 34% [ 31 ], while another study carried out in 2017 detected a prevalence of 4.4% [ 32 ]. Other studies conducted in Mexico have reported different prevalence values [ 33 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canine trypanosomiasis is a devastating disease (2) characterized by anemia, severe weight loss, muscular weakness, abortion, corneal opacity, blepharitis, conjunctivitis, keratitis and death if untreated in affected dogs (3). Trypanosomiasis of dogs was first described in 1908 (4) and it is caused mainly by Trypanosoma brucei brucei (5), Trypanosoma congolense (6), Trypanosoma cruzi (7), Trypanosoma evansi (8) and Trypanosoma caninum (9). In Nigeria, trypanosomiasis in dogs due to T. brucei and T. congolense occurs more frequently (10).…”
Section: Introductionmentioning
confidence: 99%